Initial basal cell carcinomas diagnosed in the National Campaign for Skin Cancer Prevention are smaller than those identified by the conventional medical referral system - Thweicyka Pinheiro Wakiyama; Maria Laura Marconi França; Larissa Pierri Carvalho; Mariangela Esther Alencar Marques; Hélio Amante Miot; Juliano Vilaverde Schmitt (Sociedade Brasileira de Dermatologia, 2017)
Abstract: BACKGROUND: Basal cell carcinoma is the malignant tumor most often diagnosed in the National Campaign for Skin Cancer Prevention (NCSCP). Little is known about the profile of these lesions compared to the profile of lesions diagnosed by conventional routes of public dermatological care. OBJECTIVE: To identify if basal cell carcinomas identified in prevention campaigns and referred to surgery are smaller than those routinely removed in a same medical institution. METHODS: Cross-sectional study including tumors routed from 2011-2014 campaigns and 84 anatomopathological reports of outpatients. RESULTS: The campaigns identified 223 individuals with suspicious lesions among 2,531 examinations (9%), with 116 basal cell carcinomas removed. Anatomopathological examinations revealed that the primary lesions identified in the national campaigns were smaller than those referred to surgery by the conventional routes of public health care (28 [13-50] x 38 [20-113] mm2, p <0.01). On the other hand, after a mean follow-up of 15.6 ± 10.3 months, 31% of cases identified in campaigns showed new basal cell carcinoma lesions. STUDY LIMITATIONS: Retrospective study and inaccuracies in the measurements of the lesions. CONCLUSIONS: The NCSCP promotes an earlier treatment of basal cell carcinomas compared to patients referred to surgery by the conventional routes of public health care, which can result in lower morbidity rates and better prognosis.